2023
DOI: 10.1101/2023.01.02.522438
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Incorporating models of subcortical processing improves the ability to predict EEG responses to natural speech

Abstract: The goal of describing how the human brain responds to complex acoustic stimuli has driven auditory neuroscience research for decades. Often, a systems-based approach has been taken, in which neurophysiological responses are modeled based on features of the presented stimulus. This includes a wealth of work modeling electroencephalogram (EEG) responses to complex acoustic stimuli such as speech. Examples of the acoustic features used in such modeling include the amplitude envelope and spectrogram of speech. Th… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 67 publications
0
1
0
Order By: Relevance
“…However, a recent study has shown that predictors derived from a complex model of the auditory periphery [20] that incorporates non-linear stages can lead to improved subcortical TRFs [21]. Another recent study showed that auditory-model-derived predictors outperform previously used envelope predictors even for cortical TRFs [22].…”
Section: Introductionmentioning
confidence: 99%
“…However, a recent study has shown that predictors derived from a complex model of the auditory periphery [20] that incorporates non-linear stages can lead to improved subcortical TRFs [21]. Another recent study showed that auditory-model-derived predictors outperform previously used envelope predictors even for cortical TRFs [22].…”
Section: Introductionmentioning
confidence: 99%